2024
DOI: 10.1001/jamanetworkopen.2024.4525
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile and Long-Term Risk of Depression, Anxiety, and Stress-Related Disorders

Charilaos Chourpiliadis,
Yu Zeng,
Anikó Lovik
et al.

Abstract: ImportanceBiomarkers of lipid, apolipoprotein, and carbohydrate metabolism have been previously suggested to be associated with the risk for depression, anxiety, and stress-related disorders, but results are inconsistent.ObjectiveTo examine whether the biomarkers of carbohydrate, lipid, and apolipoprotein metabolism are associated with the risk of depression, anxiety, and stress-related disorders.Design, Setting, and ParticipantsThis population-based cohort study with longitudinal data collection assessed 211 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…It's worth noting that the frequency of adult depression in the U.S. is increasing each year, affecting about 8% of adults in the U.S., and is higher in women than in men (4) .A high incidence, a high clinical cure rate but a low treatment acceptance rate and a high relapse rate are the hallmarks of depression as a mental illness. Along with cognitive abnormalities that could interfere with day-to-day learning and work, the patient may also experience hallucinations and, in extreme circumstances, suicidal thoughts (5,6).Depressed moods may cause immune, endocrine and neurological dysfunction in the body, which can increase susceptibility to disease and lead to death (7) .According to a recent meta-analysis, depression raised the probability of dying by 50% (8).However, current treatment regimens remain inadequate for some patients, and some may experience intolerable side effects, making the discovery of new depression-related bioindicators crucial for the prevention and treatment of depression.Many studies have shown that the pathogenesis of depression is closely associated with in ammation, neuroimmune dysfunction, and abnormalities in lipid metabolism (9)(10)(11)(12) .Previous ndings on the association of biomarkers in lipid metabolism with depression have however been controversial, with some studies reporting that Triglycerides (TG) have a positive correlation with the likelihood of developing depression, while low-density lipoproteins (LDL-C), total cholesterol (TC), and high-density lipoproteins (HDL-C) have a negative correlation (13)(14)(15)(16) , In contrast, Raised HDL-C levels were substantially positively correlated with depression in both sexes, according to a cross-sectional study (17) .Jane E. Persons et al concluded from a meta-analysis that there was a U-shaped relationship between LDL and depression when LDL was used as a continuous variable (18) .Non-HDL-C mainly contains cholesterol from all atherogenic lipoprotein particles, apolipoproteins, very low-density lipoprotein cholesterol (VLDL-C), and IDL-C, and relevant studies have demonstrated that the major components contained within non-HDL-C are linked to an increased risk of suffering from depression (19) . Therefore, the development of newer and more reliable lipid parameters is necessary for the prediction and management strategies of depression.…”
Section: Introductionmentioning
confidence: 99%
“…It's worth noting that the frequency of adult depression in the U.S. is increasing each year, affecting about 8% of adults in the U.S., and is higher in women than in men (4) .A high incidence, a high clinical cure rate but a low treatment acceptance rate and a high relapse rate are the hallmarks of depression as a mental illness. Along with cognitive abnormalities that could interfere with day-to-day learning and work, the patient may also experience hallucinations and, in extreme circumstances, suicidal thoughts (5,6).Depressed moods may cause immune, endocrine and neurological dysfunction in the body, which can increase susceptibility to disease and lead to death (7) .According to a recent meta-analysis, depression raised the probability of dying by 50% (8).However, current treatment regimens remain inadequate for some patients, and some may experience intolerable side effects, making the discovery of new depression-related bioindicators crucial for the prevention and treatment of depression.Many studies have shown that the pathogenesis of depression is closely associated with in ammation, neuroimmune dysfunction, and abnormalities in lipid metabolism (9)(10)(11)(12) .Previous ndings on the association of biomarkers in lipid metabolism with depression have however been controversial, with some studies reporting that Triglycerides (TG) have a positive correlation with the likelihood of developing depression, while low-density lipoproteins (LDL-C), total cholesterol (TC), and high-density lipoproteins (HDL-C) have a negative correlation (13)(14)(15)(16) , In contrast, Raised HDL-C levels were substantially positively correlated with depression in both sexes, according to a cross-sectional study (17) .Jane E. Persons et al concluded from a meta-analysis that there was a U-shaped relationship between LDL and depression when LDL was used as a continuous variable (18) .Non-HDL-C mainly contains cholesterol from all atherogenic lipoprotein particles, apolipoproteins, very low-density lipoprotein cholesterol (VLDL-C), and IDL-C, and relevant studies have demonstrated that the major components contained within non-HDL-C are linked to an increased risk of suffering from depression (19) . Therefore, the development of newer and more reliable lipid parameters is necessary for the prediction and management strategies of depression.…”
Section: Introductionmentioning
confidence: 99%